Can Cameras Stop the Killings? Racial Differences in Perceptions of the Effectiveness of Body‐Worn Cameras in Police Encounters1, 2. (31st July 2017) - Ray, Rashawn; Marsh, Kris; Powelson, Connor
Abstract : Recent killings of blacks by police have renewed a national discussion about crime, racism, unjust treatment, and implicit bias. Outfitting police officers with body‐worn cameras (BWC) is heralded by federal and state lawmakers as one solution to providing more transparency during police encounters. Missing from this discussion is what everyday citizens think about the potential effectiveness of BWC. Using data on residents of Prince George's County, Maryland, this study explores racial differences in views about police treatment and the effectiveness of BWC. We find that nonwhites report more fear of and mistreatment by the police than whites. Regarding BWC, we find that respondents are either supporters or skeptics. On one hand, respondents either believe that BWC will illuminate the difficulties of policing—police supporters—or create more transparency to hold officers more accountable for their actions—citizen supporters. On the other hand, skeptics fall into one of two types—respondents who think that BWC may put police officers more at risks—privacy skeptics—or those who do not see BWC as structurally changing the power dynamics between citizens and police officers—structural skeptics. We conclude by discussing how BWC may operate as a solution to improve interactions between citizens and the police but not necessarily alter power relations.